Behavioral Aspects of Communication in Organizations - Fortuna Casoria; Arno Riedl; Peter Werner (Institute of Labor Economics (IZA), 2020)
This paper reviews experimental studies that investigate the effects of communication on behavior in organizational settings. Two main classes of studies are identified: (a) studies on coordination and competition, which include experimental research that tests whether communication can help to overcome coordination failure within organizations, and (b) studies that analyze the role of communication in alleviating problems arising from information asymmetries at the workplace. The evidence from these studies indicates that communication is suited to improve efficient coordination within firms and to mitigate information problems in employer-employee relationships. In addition, studies are presented that focus on the interaction between communication and monetary incentive schemes in companies.
Keywords: C90; D82; D83; J53; 330; communication; organization; experiment; behavior